Nanoscale Pore Characteristics of the Lower Permian Shanxi Formation Transitional Facies Shale, Eastern Ordos Basin, North China - Wang, Zhanlei; Guo, Bingzheng; Jiang, Chan; Qi, Lin; Jiang, Yuqiang; Gu, Yifan; Fu, Yonghong; Liang, Demin (Frontiers in Earth Science, 2022)
The Lower Permian Shanxi Formation in the Eastern Ordos Basin is a set of transitional facies shale, and it is also a key target for shale gas exploration in China. Based on lithofacies classification by X-ray diffraction and kerogen type identification, nanoscale reservoir space, pore volume, pore-size distribution, surface area, fractal characterization were studied using comprehensive methods including N2 and CO2 adsorption, MICP, FE-SEM and NMR. The results indicate that Shanxi Formation shale can be subdivided into five types of lithofacies: clayey shale (Lithofacies I), siliceous clayey shale (Lithofacies II), siliceous shale (Lithofacies IV), calcareous siliceous shale (Lithofacies V) and siliceous calcareous shale (Lithofacies VI). Lithofacies V and Lithofacies VI are the best lithofacies in terms of organic pore morphology, connectivity, and development degree, followed by Lithofacies II. Inorganic pores and microfractures are well developed in all lithofacies. The majority of pores in Lithofacies I comprise of organic mesopores, but pore volume is contributed by a few in organic macropores. Pore types and pore volume contributors of lithofacies II are organic macropores. The pore size distribution of Lithofacies IV is very similar to that of Lithofacies I. Pore size distribution of lithofacies V shows typical bimodal characteristics. It is suggested that the inorganic pores of lithofacies V are mainly macropores, which have the greatest contribution to pore volume, followed by organic mesopores. TOC and thermal maturity do not present obvious controls on pore structure. Vitrinite is the main kerogen type in Lithofacies II and IV, and this is associated with disfavored morphology, low connectivity, and poor development degree of organic pores. In contrast, sapropelinite is observed in other shale lithofacies, and it is suggested to be an effective kerogen type that contributes to better development of organic pores.